PENGARUH SUHU PIROLISIS DAN JUMLAH KATALIS KARBON AKTIF TERHADAP YIELD DAN KUALITAS BAHAN BAKAR CAIR DARI LIMBAH PLASTIK JENIS POLIPROPILENA - Rio Nazif, Erlangga Wicaksana, Halimatuddahliana (Jurnal Teknik Kimia USU, 2016)
The energy usage in Indonesia generally increase by the population growth, the economic growth and technology. Today, national demands of plastic is quite large and it continues to grow by the population growth. Plastics consumption in Indonesia is about 10 kg per capita annualy. One of the methode to reuse the plastic waste is making it to the liquid fuel by pyrolisis process. It is possible to do because the plastic is consist of monomers which will form the polymer. The purpose of this study is to observe the effect of process variable (process temperature and active carbon catalyst) for yield and the quality of liquid fuel from polypropylene packaging glass plastic waste. Quality parameters that have been analyzed consist of density, specific gravity / API gravity, kinematic viscosity, heating value, Fourier Transform Infra-Red (FTIR) characteristic, Gas Chromatography - Mass Spektrofotometer (GC-MS) characteristic, the pyrolisis process was using semi batch stainless steel unstirred reactor. Pyrolysis process was used 500 gram of polypropylene (PP) packaging glass plastic waste. Then carbon active catalyst is added by ratio catalyst : propilene (w/w) were 1 :10; 1,5 : 10 ; 2 : 10 ; 2,5 : 10 ; dan 3 : 10. Temperature variables were 200 °C, 250 °C, 300 °C dan 350 °C and it’s maintained in 2 hours. The last step was condensation, then the quality parameter of liquid product was analysed. From  GC-MS analysis, the liquid product of pyrolisis most contains diesel fraction hydrocarbon that is C8 till C21. The pyrolisis temperature which produce the hydrocarbon near the best quality diesel  is at 300 °C with ratio active carbon : PP is 10:2, and the analysis to the liquid fuel product claims that the liquid fuel is near to the best quality diesel, which fullfills the standard from commercial diesel.